2014
DOI: 10.1155/2014/146028
|View full text |Cite
|
Sign up to set email alerts
|

The Tooth and Skin Colour Interrelationship across the Different Ethnic Groups

Abstract: Objectives. The purpose of the study was to investigate the relation between skin and tooth colour parameters in various ethnic groups. Materials and Methods. Saudi Arabian, Indian, African, and East Asian ethnic groups of 75 each were included in the study. The tooth colour was determined by spectrophotometer in CIELAB parameters. The skin colour was measured at earlobe, forehead, and malar locations by clinical skin photography. The data was statistically analysed by one-way ANOVA and correlation tests. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…Studies focusing on the relationship between skin tone and tooth color are sparse and they have not considered overall esthetic attractiveness. Haralur et al and Vadavadagi et al reported that tooth color was correlated with skin shade, recommending evaluating skin shade as a guide in the choice of tooth color. This recommendation has been supported by other studies reporting that people with a darker skin color have teeth with higher value and people with lighter skin color have darker teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on the relationship between skin tone and tooth color are sparse and they have not considered overall esthetic attractiveness. Haralur et al and Vadavadagi et al reported that tooth color was correlated with skin shade, recommending evaluating skin shade as a guide in the choice of tooth color. This recommendation has been supported by other studies reporting that people with a darker skin color have teeth with higher value and people with lighter skin color have darker teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The Saudi Arabian, East Asian, and Indian groups had positive linear correlation with the lightness value between tooth and skin color (31). A significant correlation was found between tooth and skin color.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Some studies suggested a significant negative relationship between skin color and tooth shade, where people with light color skin would have teeth with dark shades and people with dark skin would have whiter teeth, also, women were found to have lighter teeth color than men. [1][2][3]7,8 Other studies suggested a significant relationship of skin and tooth color as related to age, where teeth and skin darken as they get more yellow and red components. 5 On the contrary, studies tried to investigate the skin to tooth color relationship, as a reference for selecting teeth for partially or completely edentulous patients, suggested that the dentist should not consider the patient gender or complexion as fixed rules.…”
Section: Introductionmentioning
confidence: 99%